What Do Correctional Leaders Think About Faith-Based Programs? Results From a National Survey - Duwe, Grant (The prison journal, 2023)
While religious programs and services have long been a staple of the American prison experience, existing research has yet to examine how correctional administrators perceive their importance and effectiveness. Of the 50 states invited to participate in the survey, most of the 27 respondents reported that faith-based programming provides a critically important resource that yields successful outcomes and positively influences prison culture. Nearly half indicated that interest in programming exceeds the resources available, while two-thirds reported that programming access should be expanded. The vast majority cited a lack of physical space and security staff as barriers to increased programming access.